Living with Loss: Emotional Maturity and Resilience among Internal Migrant Students in Medan, Indonesia, Experiencing Paternal Loss due to Death - Khairuni Ulfayasha; Risydah Fadilah; Yudistira Fauzy Indrawan (Da'wa Faculty of Islamic State University Salatiga, 2025)
The absence of a father due to death poses profound emotional challenges, particularly for young adults navigating life away from home. This study investigates how migrant university students in Medan, Indonesia who have lost their fathers develop emotional maturity and resilience amid such loss. Conducted using a qualitative descriptive method involving three female students aged 18–25 who met specific criteria related to father loss and migration status. Participants were selected through purposive sampling, and data were obtained via interviews, observations, and document analysis. The findings reveal that the process of adaptation was gradual and non-linear, marked by periods of vulnerability alongside personal growth. Cultural values such as responsibility, perseverance, and maintaining family honor played an important role in shaping coping strategies. This research highlights that emotional maturity and resilience are built through continuous adaptation rather than formed instantly. It provides valuable insights into the lived experiences of bereaved internal migrant students and underscores the need for culturally responsive psychosocial support within academic settings.